The Coloniality of Nature: An Approach to Latin American Political Ecology (Alternautas, 2022)
A translation of ‘The Coloniality of Nature’ from the book La Naturaleza Colonizada. This piece is an examination of a particularly Latin American perspective on political ecology. In a quest for a sense Latin American identity and heritage, it looks at how the continent has been shaped since the Spanish conquest through environmental factors. It argues that human societies have been just as shaped by the traumatic destruction rendered to nature, as the environment has been shaped by said societies.